THU0018 GENETIC FACTORS AND RESPONSE TO RITUXIMAB THERAPY IN SLE. (2nd June 2020) - Liu, L.; Amar, A.; Robinson, J.; Bruce, I. N.; Morris, D.; Vyse, T.
Abstract : Background: The biologic drug Rituximab (anti-CD20) is used therapeutically in SLE, however the clinical response to the therapy, which is expensive, is quite variable. Factors influencing the efficacy have been challenging to determine. The MRC funded MASTERPLANS consortium has investigated prognostic factors that determine the therapeutic response to biologic therapy in SLE. Genetics has not been studied on a large scale in this context. SLE is a complex clinical phenotype, it is likewise a complex genetic trait, although it has recently been shown that polygenic risk scores do have a relationship to the severity of the disease (1). In addition, genetic risk factors for SLE, coded at the IgG Fc gamma receptor locus, have the potential to influence antibody-dependent cell-mediated cytotoxicity. Objectives: To determine whether the genetics influences the clinical outcome of therapy with Rituximab. The study used both genome-wide data in the form of genetic risk scores as well as specific genetic data at a candidate locus, namely the IgG Fc gamma receptor locus Methods: Samples from the BILAG Biologics Register (BILAG BR) of individuals treated with Rituximab were subject to genome-wide genotyping with Illumina GSA V2 chip. Genetic risk scores (GRS) were calculated through a weighted risk sum. Genetic variation at the IgG Fc gamma receptor locus is not captured well on genotyping chips and hence common coding and copy number variation was studied using Multiplex Ligation-dependent Probe Amplification (MLPA) and sequencing. Results: BILAG-BR samples for SLE part of receiving Rituximab therapy were genotyped on GSA chip, 573 samples passed QC and were used in principal components analysis (PCA), among them, 310 samples both have RTX treatment information and GRS calculated. Examining the population using PCA in the informative samples revealed that the largest distinction, European versus African ancestry did not correlate with Rituximab response. When GRS was determined in the Responders versus the Non-responders there was a weak correlation with those with a higher risk score showing a tendency to be in the responder group (Fig. 1 ). We also examined variation at the IgG Fc gamma receptor locus, polymorphisms of which are associated with SLE and have been correlated with therapeutic outcome in lymphoma (2). In a subset of the BILAG-BR cohort, we show that carriage of the SLE risk allele at FCGR3A (158F) was enriched in the 'responder at some point' group compared to the non-responder group (P=0.03, Chi-square). Conclusion: We present preliminary data indicating that genetics at both the genome wide level and at the FCGR locus show some influence on the outcome of therapy with Rituximab in SLE; more data are required in order to draw firm conclusions. References: [1]Reid S et al. High genetic risk score is associated with early disease onset, damage accrual and decreased survival in systemic lupus erythematosus. Ann Rheum Dis. 2019 Dec 11. [Epub ahead of print] [2]Weng WK, Levy R. Two immunoglobulin G fragment C receptor polymorphisms independently predict response to rituximab in patients with follicular lymphoma. J Clin Oncol. 2003;21(21):3940–3947. Acknowledgments: King's and GSTT Biomedical Research Centre and M01665X/1MRC Stratified Medicine grant Disclosure of Interests: Lu Liu: None declared, Ariella Amar: None declared, James Robinson: None declared, Ian N. Bruce Grant/research support from: Genzyme Sanofi, GSK, and UCB, Consultant of: Eli Lilly, AstraZeneca, UCB, Iltoo, and Merck Serono, Speakers bureau: UCB, David Morris: None declared, Tim Vyse: None declared